Changes over 26 years in the avifauna of the Bogotá region, Colombia: Has climate change become important? (2017)
High Neotropical mountains are among the most threatened ecosystems by climate change and this problem could be accentuated in cities where temperatures are higher. However, there are few data of long-term avifaunal changes in Neotropical cities, and the potential impact of climate change has yet to be addressed. Using data from 26 years of Audubon's Christmas Bird Counts (CBCs) in the Bogotá area (ca. 2,600-3,100 m in Colombia's eastern Andes), we analyze long-term changes of the avifauna using linear regressions corrected for species' habitat preferences and compared urban and rural sites. For the CBC we followed the National Audubon Society's methodology in which birds are counted over a 24-h period within a fixed circle 24 km in diameter. We recorded 235 species in the Bogotá circle with an average of 122 spp/year, including 46 boreal migrants, three endemic species, and four endemic subspecies, two globally and four locally threatened species. Species richness was higher in rural than in urban areas and most species were associated with native forest and scrub and wetlands. Among the species that were analyzed for changes in time 31% increased, 20% decreased, and 49% did not change. Strong fluctuations or changes in abundance were more frequent in urban than rural environments. Many of the species that increased or became established during the CBC interval came from lower elevations or the warmer, drier parts of the region beyond the count circle. By contrast, the lower elevational limits moved to higher elevations in several species that decreased. Climate change with its related effects represented the factor associated with the most changes in abundance. Other potential causes were direct human actions, mostly associated with urbanization, and "natural" successional changes in vegetation; predation by feral dogs and cowbird parasitism also affected several species negatively. Observations indicate that these factors will continue into the future, and the effects of climate change and urbanization in particular will probably intensify. The Bogotá CBC has provided much valuable information for Neotropical urban ornithology and its practice should be encouraged in other Latin American cities and should definitely continue in Bogotá for many years to come. © 2017 Stiles, Rosselli and De La Zerda.